Correction to: Randomized community trial on nosocomial infection control educational module for nurses in public hospitals in Yemen: a study protocol - Gamil Alrubaiee; Anisah Baharom; Ibrahim Faisal; Kadir Shahar Hayati; Shaffe Mohd. Daud; Huda Omer Basaleem (BMC, 2019)
In the original publication of this article [1], a formula's format in the section of "Sample size calculation" was wrong and needs to be revised.